Psychological peculiarities of professionally successful sportsmen of national teams of russia: intersex distinctions analysis - Sevostyanova, M. S.; Loginova, I. O. (The Russian Journal of Physical Education and Sport, 2018)
The article is about the urgent problem of searching for psychological conditions of effective professionalization in elite sport. The results of psychological peculiarities empirical study, which distinguish professionally successful sportsmen and female athletes of high qualification from other athletes of the same sex, are presented. Comparative analysis of psychological profiles of professionally successful sportsmen- men and women are presented. Materials. Objective medical-psychological data about the level of psychic adaptation of 354 sportsmen from national teams of Russia, results of questionnaire and psychological testing. Research methods: 1) medical documents analysis; 2) clinical-psychological methods: observation, structured interview, questionnaire survey using specially created author`s questionnaire "My sports career"; 3) psychognostic testing; 4) methods of mathematical statistics: Mann-Whitney U test. Results. Several formal-dynamic and personal psychological characteristics for male and female sample groups, owing to which sportsmen manage to preserve a high level of psychic adaptation, were defined. For example, for men these characteristics were the following: motor plasticity, communicative speed, motor emotionality, involvement, control, risk acceptance, self-transcendence, freedom, responsibility, existentiality, single-mindedness, modeling, masculinity, androgyny. For women these characteristics were the following: intellectual plasticity, intellectual ergicity, motor plasticity, motor speed, involvement, control, risk acceptance, single-mindedness, balanced development, responsibility, activity structuring fixation, orientation toward present, modeling, planning, programming, flexibility. Also, characteristics were defined, which distinguish sportsmen with stable high sports results. For men these characteristics are the following: motor ergicity, intellectual ergicity, motor emotionality, communicative emotionality, self- distancing, self-transcendence, personality, activity structuring fixation, perseverance, planning,programming. For women these characteristics are the following: personality, modeling, independence and femininity. Comparative analysis of psychological profiles of professionally successful men and women didn`t reveal valid differences in the indices values of components of vitality and emotional peculiarities, which prove the features of alexithymia. Insignificant differences were in the intensity of the separate formally dynamic features of individuality. Maximum intergroup differences were revealed according to the indices of the profile of existential performance, skills of self-regulation, self-organization and gender characteristics. Conclusion. The received results can be used for psychogram of professionally successful highly